2021
DOI: 10.1016/j.jstrokecerebrovasdis.2020.105428
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Hemorrhage in Hospitalized SARS-CoV-2 Patients: A Case Series

Abstract: The SARS-CoV-2 virus causing Coronavirus Disease 2019 (COVID-19) is a global pandemic with almost 30 million confirmed worldwide cases. Prothrombotic complications arising from those affected with severe symptoms have been reported in various medical journals. Currently, clinical trials are underway to address the questions regarding anticoagulation dosing strategies to prevent thrombosis for these critically ill patients. However, given the increasing use of therapeutic anticoagulation in patients admitted wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…Recently, Mousa-Ibrahim and cols [ 8 ] reported intracranial hemorrhage as well as thrombosis within six COVID-19 patients. Moreover, in an exceptional review study, Pramitasuri and cols.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Mousa-Ibrahim and cols [ 8 ] reported intracranial hemorrhage as well as thrombosis within six COVID-19 patients. Moreover, in an exceptional review study, Pramitasuri and cols.…”
Section: Discussionmentioning
confidence: 99%
“…Cerebral hemorrhagic complications and retroperitoneal and adrenal gland hemorrhages have also been described. 17,18 An emerging presentation of COVID-19 can also be hemoptysis. 19,20 Peys et al 19 reported a case of a COVID-19 patient with an acute onset of hemoptysis and alveolar hemorrhage on CT.…”
Section: Discussionmentioning
confidence: 99%
“…Cerebral hemorrhagic complications and retroperitoneal and adrenal gland hemorrhages have also been described. 17 , 18 …”
Section: Discussionmentioning
confidence: 99%
“…10,11 CAC is characterised by a prothrombotic state 12 entailing clinical hypercoagulopathy and thromboembolism on the one hand, but also bleeding and intracranial haemorrhage due to endothelial leakage. 1319 Therefore, anticoagulation in COVID-19 patients is pivotal, and not trivial. 12,20…”
Section: Introductionmentioning
confidence: 99%